2015
DOI: 10.1007/s00300-014-1642-3
|View full text |Cite
|
Sign up to set email alerts
|

Macrobenthos of the Ob Bay and adjacent Kara Sea shelf

Abstract: The southeastern part of Kara Sea is a highly dynamic area influenced by freshwater masses of Ob and Yenisei rivers. It is possible to estimate the annual changes of bottom communities in such areas by studying the temporal and spatial distribution of benthic organisms. In the previous studies of the same areas, the communities differing essentially in the composition and abundance were described mainly due to the different sampling methods employed and possible temporal changes in the macrobenthos. The aims o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 18 publications
5
19
0
2
Order By: Relevance
“…A number of published studies on macrofauna on the Siberian shelf showed an increase of species richness and diversity from the upper shelf to the shelf edge [48,5962]. Besides the explanation of this peak in diversity and richness by the “polar emergence” theory explained above, we also suggest that food availability by higher productivity of the ice margin zone is a key factor.…”
Section: Discussionsupporting
confidence: 62%
“…A number of published studies on macrofauna on the Siberian shelf showed an increase of species richness and diversity from the upper shelf to the shelf edge [48,5962]. Besides the explanation of this peak in diversity and richness by the “polar emergence” theory explained above, we also suggest that food availability by higher productivity of the ice margin zone is a key factor.…”
Section: Discussionsupporting
confidence: 62%
“…A number of published studies on macrofauna on the Siberian shelf showed an increase of species richness and diversity from the upper shelf to the shelf edge [ 48 , 62 65 ]. Besides the explanation of this peak in diversity and richness by the “polar emergence” theory explained above, we also suggest that food availability by higher productivity of the marginal ice zone is a key factor.…”
Section: Discussionmentioning
confidence: 99%
“…In the southern Kara Sea the Ob–Yenissean mouth CPA (area 26, Figure a) ecosystem provides an example of an ecosystem governed by river runoff and advection of transformed riverine waters and estuarine fronts. Taxonomic diversity and biomass of communities follow the actual (for plankton) and averaged over time (for benthos) salinity gradient (Galkin, Kucheruk, Minin, Raiskyi , & Goroslavskaya, ; Polyak et al, ; Stepanova, ; Vedenin, Galkin, & Kozlovsky, ; Vinogradov, Shushkina, Lebedeva, & Gagarin, ). The main estuarine front is located in the mouth of the Ob Gulf and extends offshore to a distance of about 100 km.…”
Section: Discussionmentioning
confidence: 99%